The ten trusts : what we must do to care for the animals we love - Goodall, Jane, 1934-; Bekoff, Marc. (San Francisco : HarperSanFrancisco, 2002)
Presents ten trusts, or mentras, designed to make people think about their role as custodians of the planet, identifying humans as part of the animal kingdom and urging respect for all species.
Includes bibliographical references (p. [187]-200).
Adult
Adult
Wilson's Senior High School
School Library Journal
Library Journal
Keywords: Human-animal relationships; Animal rights; Animal welfare; Wildlife conservation; Nature -- Effect of human beings on; Animal rights; Animal welfare; Wildlife conservation; Human influence on nature